A Review on Coconut Coir as Thermal Insulation Material in Building Application - NURUL HAYATUL SAHIRA; Masni A.Majid (Recent Trends in Civil Engineering and Built Environment, 2021)
Over the previous few centuries, there has been a worldwide growth in energy consumption for cooling and heating in buildings. Therefore, researchers and building professionals has proposed the solution to use renewable resources from agricultural waste where it can developed to keep the building at the right temperature for a long period. The agriculture waste that are focused in this study for the thermal insulation building is coconut coir. The objective of the study are to review the availability potential of coconut coir that use in the building application and to study the effectiveness of the thermal properties of coconut coir in building application. The thermal insulation that will be cover in this study are thermal conductivity (U), thermal resistance (R) and thermal transmittance (U). Four parameters cover for the thermal conductivity which is coir content, coir length, bulk density and size of sand. To reach the study’s goal, about 50 literature papers from previous research were examined and compared to meet the study’s purpose. Found that the optimum of coir content is about 10% w/w which give the lowest thermal conductivity, 0.24 W/mK. Using < 2mm length of the coconut coir give the lowest value thermal conductivity value is 0.20 W/mK. The highest of the bulk density which is 1350 kg/m3 give the highest thermal conductivity value ; 0.6736 W/mK. For the size of sand, using <0.71 mm with the length of coir <2 mm will give the lowest thermal conductivity which is 0.195. The density of 65 kg/m3 will make the R-value higher; 2.52 m2℃/W and the thickness of 0.08 m give the U-value 0.21 W/m2K. Hence, coconut coir fiber is recommended to use in the building application because of their lower thermal conductivity, thermal transmittance and higher thermal resistance.